The influence of women directors on Enterprise Innovation - Based on the diversification of the board of directors - Zhang, Ying (2024)
The board of directors in corporate governance is crucial. It serves as a decision-making body within a company, linking shareholders and management. Core board responsibilities include protecting shareholder interests, crafting strategies, overseeing management, and ensuring governance. Research on board structure is significant in theory and practice due to its implications. Board diversity reveals varied member attributes. Contemporary theories suggest board members' characteristics affect decisions and performance. Scholars explore how diversity, including age, tenure, experience, education, and beliefs, impacts outcomes (Conyon & Mallin, 1997).